Interplay of strategic orientations in the development of smart solutions - Huikkola, Tuomas; Kohtamäki, Marko (Elsevier, 2019)
This study investigates the different strategic orientations available for technology companies that provide smart solutions to their clients. We conceptualize eight archetypes of approaches employed by technology companies to develop smart solutions based on three strategic orientations: 1) entrepreneurial, 2) technology, and 3) market (customer). In our analysis, we examine the interplay of these orientations in leading technology companies that are developing smart solutions. Our findings reveal that smart solutions can potentially facilitate technology firms to synchronize their strategic orientations through improved organizational learning capability. Furthermore, suggestions for managers and the study’s limitations are discussed.
Keywords: smart solutions; digital servitization; strategic orientation; digitization; Internet of Things; fi=Johtaminen ja organisaatiot|en=Management and Organization|